Key to species of the genus Pachymetopius Matsumura (Hemiptera: Cicadellidae: Stegelytrini ) with description of a new species from China - Wei, Xingtao; Xing, Jichun; Webb, Michael D. (Zootaxa, 2019)
A new leafhopper species: Pachymetopius falcatus sp. nov., is described and illustrated from Guizhou Province, China. A key is given to distinguish all species of the genus. The type specimen of the new species is deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).